Identification of natural zeolite from Sukabumi, West Java, Indonesia: structure, chemical composition, morphology and molecular vibration. (6th June 2017) - Wibowo, E; Rokhmat, M; Sutisna,; Murniati, R; Khairurrijal,; Abdullah, M
Abstract: Characterizations of natural zeolite from Sukabumi were carried out using x-ray diffraction spectroscopy, energy dispersive x-ray spectroscopy, scanning electron microscopy, the Brunauer–Emmet–Teller method and Fourier transform infra-red spectroscopy to identify the structure, chemical composition, morphology, surface area and molecular vibration of zeolite. We determined that the type of zeolite was clinoptilolite with a high degree of crystallinity and high specific surface area. The full width at half maximum, crystal size, strains, specific surface area, pore volume and pore diameter of zeolites were 0.85°, 18.94 nm, 0.009, 31 266 m 2 g −1, 0.089 cc g −1, and 3.811 nm, respectively. The Si/Al ratio of >4.0 (4.61) indicated that the zeolite had relatively high thermal resistance. Natural zeolite with a high degree crystallinity and high thermal resistance is suitable, activated through thermal process, for enhancing its sorption ability.